Apo B/Apoa1 Ratio is Statistically the Best Predictor of Myocardial Infarction Compared to Other Lipid Ratios - DR. RAJNI DAWAR; DR. ANIL GURTOO; DR. RITU SINGH (International Journal of Pharma and Bio Sciences, 2010)
The aim of our work was to study the predictive value of various lipid ratios in patients with Myocardial Infarction (MI). Study group with 60 patients of documented myocardial infarction and 60 healthy controls were enrolled. Extended lipid profile with Serum Apolipoprotein A and Apolipoprotein B was undertaken for each subject. Lipid ratios of LDL/HDL, TC – HDL/HDL, TG/HDL-C and Apo B/Apo A1were calculated and statistically evaluated to determine the best predictor of MI amongst them. All the above ratios were significantly higher in cases compared to the controls (p<0.0001for all). On multiple regression analysis, the best predictor for MI was Apo B/Apo A1 ratio. The coefficient Beta for ApoB/Apo A1 was 0.691 with t value of 9.916 showing highly significant prediction of MI (p<0.000). Based on our findings we advocate the use of ApoB/Apo A1 ratio in Indian Population for assessing risk of MI.